Karl Rahner. "Pozabljanje na Boga - najbolj temeljni problemi tudi danes" - Zinrajh, Zvonko (Anthropos (Ljubljana), 2011)
There are many scientists who affirm Karl Rahner as one of the most important world's theologians, who triggered, because of his characteristic approach and his sometimes margin-walking theory, a lot of criticism. Based on his gigantic write, the assessors are taking him as a traditionalist, who inhis research and quest of Christian truth discovers the ways which can be the ground for a mistaken understanding (comprehension) of faithćs doctrine and moral teachings. Rahner's interesting mind about the pluralism of theology could also be a cause of bewilderment, which was the case with cardinal Balthasar's critics against some Rahner's statements. In his traditional approach, Rahner placed great emphasis on incarnation and eschatology as well as mediation. Exceptional contribution to the Church was given in his discussions on and viewpoints of Godćs mercy, naturalness, sacraments and Godćs works. He also paid attention to the common connections between Catholic Church and Orthodox and Evangelical (Protestant) Church and treatises on the importance of ecumenical dialog. In his books, Rahner ascertains that Christianity, although it addressed all people and had the ambition of becoming a world religion, was able to live by itself, based on its own historical roots. But the Christianity wants to be a world religion and actually has a great opportunity to be one. As a World Religion, the Christianity could open one of the ways to solve perhaps the most fundamental problem of today: forgetting of God.
Keywords: Rahner, Karl, 1904-1984; religija; religion; Christianity; krščanstvo; krščanska teologija